HUBUNGAN MINAT PRESTASI PRAKTIK KERJA LAPANGAN DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII JASA BOGA SMK - Christina Bety Sukesi (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
The purpose of this study was to find out: (1) achievement of field work practice, (2) interest in entrepreneurship, and relationship between the achievements of fieldwork practice. This type of research is